STRATEGI INOVATIF DESAIN KURIKULUM DALAM PENGEMBANGAN NUMERASI PESERTA DIDIK DI SDN POGAR II BANGIL: Penelitian Kualitatif STRATEGI INOVATIF DESAIN KURIKULUM - Ainul Yaqin; Muhammad Junaedi; Nurul Hidayati; Kukuh Widyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe curriculum management innovations implemented in strengthening numeracy learning to support the Profile of Pancasila Students at SDN Pogar II Bangil. The background of this research stems from the low numeracy performance identified through diagnostic assessments and the need for systematic curriculum management aligned with the principles of the Merdeka Curriculum. A qualitative descriptive method was applied by conducting observations, interviews, and documentation studies. The results indicate that curriculum innovations were implemented through adaptive learning planning, differentiated learning strategies, project-based numeracy enrichment, and digital learning integration. These innovations proved to enhance students’ numeracy engagement and problem-solving abilities. The study concludes that curriculum management innovation is essential to strengthening numeracy competencies and effectively supporting the realization of the Pancasila Student Profile